Description and analysis of adsorption heat storage device - Stritih, Uroš (Strojniški vestnik, 2014)
In this study, the main goal was to develop an adsorption heat storage system for domestic heating system gained by solar collectors and to indicate a new way of maintaining the energy. Main characteristic of the storage system is to retain the energy for a longer period, as long as the adsorbent and adsorbat are separated. This research analysis the influence of several parameters on the adsorption heat storage system such as: the quantity of the stored heat, the in- and out-flowing water temperatures, the water mass flow and the saturation of the adsorbent. Adsorbent HX-13 sodium aluminosilicate Na2O Al2O3 * 2SiO2 in the form of granule was used. Regarding the results we can be conclude that the low adsorption heat storage is low hydrophilic characteristic of the used adsorbent.
Keywords: adsorbati; adsorbenti; aluminosilikati; eksperimenti; shranjevalniki toplote; termo-kemično shranjevanje